Comparison of Antibiotic Regimens in Intra-abdominal Infections. (4th October 2017) - Hasanoglu, Imran; Guner, Rahmet; Bilmez, Ruveyda; Kayaaslan, Bircan; Buzgan, Turan; Tasyaran, Mehmet A
Abstract: Background: Appropriate antimicrobial therapy and sometimes urgent surgery are life-saving in intra-abdominal infections (IAI). Methods: We performed a retrospective case control study to evaluate the efficacy of ceftriaxone, ceftriaxone plus metronidazole, tigecycline, and ertapenem regimens in IAI. Patients aged >18 years and diagnosed with IAI between 2015 and 2017 are included in the study. Definitions are based on IDSA IAI guideline. Significant resolution of all signs and symptoms of IAI with no further need for antimicrobial therapy or surgical intervention for infection is accepted as clinical response (CR). Microbiological response (MR) is assessed among patients with positive culture and defined as documented or presumptive microbiological eradication of pathogen. Results: 659 patients are included in the study. Mean age was 56 years. Source control was maintained in 45.5% of patients. Among 54 patients with available culture specimen, E.coli was the most isolated pathogen (81% ESBL +). Comparisons of antibiotics in all patients and in complicated IAI are shown in Table 1 and 2, respectively. Conclusion: Ertapenem, and especially tigecycline are good options in IAI in the era of high antimicrobial resistance. Disclosures: All authors: No reported disclosures.